Implementation of Civil Environmental Law Enforcement in Cases of River Pollution Caused by Industrial Activities - Valencia Prasetyo Ningrum; Mella Ismelina Farma Rahayu (Jurnal Pendidikan Indonesia, 2024)
In various cases related to environmental problems, usually industry is the most dominant subject as the mastermind that causes a decline in the quality of the environment in a certain area or community environment. This is inseparable from the economic activities of the community that are increasingly depleting natural resources. This can certainly be a trigger for disputes between industry and society. Awareness of the environment does not only create everything beautiful and clean, but here there is an obligation from every human being to respect and appreciate the rights of others and the surrounding life. However, often many people are less responsible in disposing of waste so that it is not uncommon to cause environmental pollution, which will later harm people around the industry. In the past, humans lived without worrying about disturbances or dangers that would cause air pollution, water pollution or environmental pollution by an industrial activity. But now, along with the development of science and technology, people often feel worried about the disruption of their lives. Even before technology developed, humans with their living environment felt more comfortable. But the development of the present era has presented many industries with all kinds of activities. One way to enforce environmental laws in order to have a deterrent effect is through civil law. However, often dispute resolution through civil is not popular with the Indonesian people, this is because the process takes a long time.